BASIC METHODS AND PRINCIPLES OF REFLEXIVE EDUCATION IN HIGHER EDUCATION (Proceedings of International Educators Conference, 2023)
One of the most convenient aspects of using modern technologies of education in harmony with reflection is that it involves two-way activity. The activity of the teacher-pedagogue controls the reflexive processes during the lesson and shows that it is a guarantee of the non-emergence of negative relations, at the same time, it maintains the health importance of the lesson. As a result of reflexive activity of students, the teacher realizes the level of his personal and professional qualities, and the opportunities to determine the level of activity of students during the lessons expand even more. According to the definition of G.S. Pyankova, the activity of students in reflexive education takes place in two stages